The Influence of Language Competence, Literacy, Local Wisdom and Multimedia in Developing the Tourism Potential of Pematang Serai Village - Yunus, Rusyda Nazhirah; Putri, Ranti Eka; Ramadani, Mutiara (International Journal of English and Applied Linguistics (IJEAL), 2024)
The tourism industry, when viewed from a cultural perspective, indirectly has a significant role in the development of Indonesian culture. The rapid growth of the tourism industry allows interaction between tourist visitors and local communities in the tourist area. This allows tourists to understand and appreciate the local culture and cultural background of the local community. Language and literature have an important role in preserving local wisdom and introducing it to the public or readers. In the context of local wisdom, it is important to understand the history and development of Indonesian life. The understanding of local characters and values has always been the focus of attention in every era and generation that contributed to the journey of this nation. The research method used is descriptive quantitative method with data collection techniques in the form of questionnaires, documentation and interviews, the data analysis used is the data analysis technique according to Milles and Huberman. The results of the research For the development of local wisdom-based tourism in Pematang Serai, it is necessary to have a more detailed plan in the form of a masterplant for local wisdom-based tourism development in strengthening the character and economy of the Pematang Serai Village community. In practice, language and literature are able to strengthen positive local values in the thoughts and feelings of the Indonesian people. language is able to become a filtering tool or filtering influences from outside.Development of tourism based on Language, Literature, Multimedia and Local Wisdom in Pematang Serai Village can be done with three dimensions: the dimensions of geol (getek online) beaches and marine and Culture / Customs and Beliefs.